2023
DOI: 10.1111/odi.14540
|View full text |Cite
|
Sign up to set email alerts
|

Recombination humanized type III collagen promotes oral ulcer healing

Abstract: ObjectiveRecombinant humanized type III collagen (rhCol III) is a highly adhesive biomaterial composed of 16 adhesion‐related tandem repeats refined from human type III collagen. Here, we aimed to investigate the effect of rhCol III on oral ulcers and reveal the underlying mechanism.MethodsAcid‐induced oral ulcers were induced on the murine tongue, and rhCol III or saline drops were administered. The effect of rhCol III on oral ulcers was assessed using gross and histological analyses. The effects on the proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 40 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Collagen possesses a characteristic triple-helical structure, composed of three polypeptide chains known as α-chains ( Mi et al, 2018 ; Rappu et al, 2019 ). In vitro studies have recombinantly produced different types of collagens from isolated genes, including types I, II, III, and V collagen ( Woodley et al, 2017 ; Doan et al, 2019 ; Shuai et al, 2023 ). Compared to natural collagen, recombinantly produced collagen achieves proper post-translational modifications, including hydroxylation and glycosylation ( Shekhter et al, 2019 ; Deng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Collagen possesses a characteristic triple-helical structure, composed of three polypeptide chains known as α-chains ( Mi et al, 2018 ; Rappu et al, 2019 ). In vitro studies have recombinantly produced different types of collagens from isolated genes, including types I, II, III, and V collagen ( Woodley et al, 2017 ; Doan et al, 2019 ; Shuai et al, 2023 ). Compared to natural collagen, recombinantly produced collagen achieves proper post-translational modifications, including hydroxylation and glycosylation ( Shekhter et al, 2019 ; Deng et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…These rhCol III exhibits similar properties and stability as natural human collagens, and offers several advantages including ease of obtainment, good water solubility, low immunogenicity, absence of hidden virus risks, and a stable production process. 22,23 It has drawn a lot of interest from the food, cosmetics, and pharmaceutical industries, [24][25][26][27][28] and has been investigated as bioactive materials in various tissue regeneration. [29][30][31][32][33] It is also reported that rhCol III was highly effective for wound healing.…”
Section: Introductionmentioning
confidence: 99%